2014
DOI: 10.1007/s40750-014-0015-z
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Competitiveness: Hunter-Gatherer Women and Girls Compete Less in Gender-Neutral and Male-Centric Tasks

Abstract: Despite numerous attempts to increase workplace equality, the near universal gender wage gap and underrepresentation of women in high status jobs persists in societies around the world. This persistence has led some researchers to speculate that psychological sex differences may be partly to blame. In particular, economists have begun to focus on sex differences in competitiveness as a possible cause. Here we test whether sex differences in competitiveness exist in a relatively isolated and evolutionarily rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 72 publications
5
31
0
1
Order By: Relevance
“…However, we failed to find associations between 2D:4D and aggression/dominance measures in Hadza men and Datoga men and women. Our finding on sex differences in the association between2D:4D and dominance are in line with recent findings (Apicella and Dreber, 2014), showing that the willingness to compete, among women, was positively related to the number of children born, while such an association was not found in men. Studies of 2D:4D and aggression in Western samples revealed negative relationships between 2D:4D and aggression (H€ onekopp et al, 2006a) and dominance (Manning and Fink, 2008), leading to the conclusion that 2D:4D may facilitate intra-sexual competition and promiscuity (H€ onekopp et al, 2006b).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, we failed to find associations between 2D:4D and aggression/dominance measures in Hadza men and Datoga men and women. Our finding on sex differences in the association between2D:4D and dominance are in line with recent findings (Apicella and Dreber, 2014), showing that the willingness to compete, among women, was positively related to the number of children born, while such an association was not found in men. Studies of 2D:4D and aggression in Western samples revealed negative relationships between 2D:4D and aggression (H€ onekopp et al, 2006a) and dominance (Manning and Fink, 2008), leading to the conclusion that 2D:4D may facilitate intra-sexual competition and promiscuity (H€ onekopp et al, 2006b).…”
Section: Discussionsupporting
confidence: 93%
“…Hadza are known for their egalitarianism and lack of formal leadership, and remained so nowadays. Yet they bear competitive potential, and men were found to be more competitive and willing to win in competitive tasks than women (Apicella and Dreber, 2014). Marginalization processes are less severe in the neighboring Datoga, although they have been exposed to the same environmental stressors.…”
Section: Discussionmentioning
confidence: 99%
“…The gender gap in competitiveness appears to be stronger in mixed-sex competition than in single-sex competition or in self-competition (see, e.g., Gneezy et al, 2003, Niederle et al, 2013, and Apicella et al, 2017. The gender gap seems to emerge at an early age (see, e.g., Rustichini, 2004, andGlätzle-Rützler andSutter, 2014), and to exist in diverse societies (see, e.g., Gneezy et al, 2009, Apicella and Dreber, 2015, and Zhang, 2018. Gender differences in competitiveness have also been documented outside the laboratories (see, e.g., Buser et al 2014, Reuben et al, 2015, and Zhang, 2018.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…1The fact that women to a significantly higher extent than men opt out of this type of competitions has been documented in many (but not all) societies and across age groups (e.g., Gneezy et al 2009; Cárdenas et al 2012; Flory et al 2012; Mayr et al 2012; Andersen et al 2013; Almås et al 2015; Apicella and Dreber 2015; Sutter and Glätzle-Rützler 2015), and this tendency appears to be particularly strong for math-related tasks (Günther et al 2010; Grosse and Reiner 2010; Dreber et al 2014). See Flory et al (2010) for a field experiment in a real labor market.…”
mentioning
confidence: 99%